La impunidad en América Latina llevada a juicio por el Tribunal Permanente de los Pueblos - Simona Fraudatario (Les Cahiers ALHIM)
The article is about the main contributions of the session on The impunity of the crimes against humanity in Latin America that the Permanent Peoples’ Tribunal (PPT) held between 1989 and 1991, following the request of social actors and movements whose intention was to make visible the persistence of violence and the significant human rights abuses, in order to understand their causes and the mechanisms that made them possible. In particular, the article will highlight those elements of the complaints presented that illustrate the link between truth and justice and the democratic project proposed by the social movements. The session will be considered as point of arrival of the process of clarification of the truth that began with the Russell Tribunal on the dictatorships in Latin America of the 70s.